Post-exercise high-sensitivity troponin T levels in patients with suspected unstable angina. - Gaetano Antonio Lanza; Erica Mencarelli; Veronica Melita; Antonio Tota; Maurizio Gabrielli; Filippo Sarullo; Chiara Cordischi; Annalisa Potenza; Silvia Cardone; Antonio De Vita; Antonio Bisignani; Laura Manfredonia; et al. (PLoS ONE, 2019)
BACKGROUND:Previous studies showed that troponin blood levels may increase after exercise. In this study we assessed whether, among patients admitted with suspected unstable angina, the increase in high-sensitive troponin T (hs-TnT) levels after exercise stress test (EST) might help identify those with obstructive coronary artery disease (CAD) and predict symptom recurrence during short term follow-up. METHODS:Maximal treadmill EST was performed in 69 consecutive patients admitted to the emergency room with a suspicion of unstable angina (acute chest pain but confirmed normal serum levels of cardiac troponins) was measured before and 4 hours after EST. Coronary angiography was performed in 22 patients (32.8%). RESULTS:hs-TnT increased after EST compared to baseline in the whole population (from 0.84±0.65 to 1.17±0.87 ng/dL, p<0.001). The increase was similar in patients with positive (n = 14) and negative (n = 55) EST (p = 0.72), and was also similar in patients with (n = 12) and without (n = 10) obstructive CAD at angiography (p = 0.91). The achievement of a heart rate at peak EST ≥85% of that predicted for age was the variable mainly associated with the post-EST hs-TnT increase at multivariable linear regression analysis (p = 0.005). The change after EST of hs-TnT did not predict the recurrence of symptoms or readmission for chest pain at 6-month follow-up. CONCLUSIONS:Our data show that hs-TnT increased after EST in patients with suspected unstable angina, which seemed largely independent of most clinical and laboratory variables. Thus, hs-TnT assessed after EST does not seem to be helpful to identify patients with obstructive CAD in this kind of patients.